CO2 emissions, energy consumption, economic growth, and financial development in GCC countries: Dynamic simultaneous equation models - Bekhet H.A.; Matar A.; Yasmin T. (Elsevier Ltd, 2023)
Carbon dioxide; Decision making; Economic analysis; Economics; Energy utilization; Finance; Causal relationships; Environmental aspects; Financial development; Gcc countries; Gross domestic products; Gulf Cooperation Council; Simultaneous equation models; United Arab Emirates; Economic and social effects